Micronutrient supplementation affects transcriptional and epigenetic regulation of lipid metabolism in a dose-dependent manner. Issue 11 (2nd November 2021) - Saito, Takaya; Whatmore, Paul; Taylor, John F.; Fernandes, Jorge M.O.; Adam, Anne-Catrin; Tocher, Douglas R.; Espe, Marit; Skjærven, Kaja H.
ABSTRACT: Micronutrients (vitamins and minerals) have been less well studied compared to macronutrients (fats, proteins, and carbohydrates) although they play important roles in growth, metabolism, and maintenance of tissues. Hence, there is growing interest to understand the influence of micronutrients across various aspects in nutritional research. In the last two decades, aquaculture feeds have been shifted to containing more plant-based materials to meet the increasing demand and maintain the sustainability in the industry. A recent whole life cycle feeding trial of Atlantic salmon ( Salmo salar ) with graded levels of micronutrient packages has concluded that the levels of several B-vitamins and microminerals need to be increased from the current recommendation levels for optimal growth and fish welfare when plant-based diets are used. Here, we show the effect of micronutrient supplementation on hepatic transcriptional and epigenetic regulation in a dose dependent manner. . Specifically, our aim is to reveal the mechanisms of altered cell metabolism, which results in improved growth performance by micronutrient surpluses, at gene expression and DNA methylation levels. Our results strongly indicate that micronutrient supplementation suppresses gene expression in lipid metabolism in a dose-dependent manner and broadly affects DNA methylation in cell-adhesion and cell-signalling. In particular, it increases DNA methylation levels on the acetyl-CoA carboxylase alpha promoter in a concentration-dependent manner, which further suggests that acetyl-CoA carboxylase alpha is an upstream epigenetic regulator controlling its downstream lipid biosynthesis activities. This study demonstrates a comprehensive analysis to reveal an important role of micronutrients in lipid metabolism through epigenetic control of gene expression.